Distally based medial adipofascial flap for medial leg defects: An orthopedic-led orthoplastic experience - Touloupakis, Georgios; Lettera, Maria Gabriella; Theodorakis, Emmanouil; Gilli, Antonio; Ghirardelli, Stefano; Antonini, Guido (Acta Biomedica Atenei Parmensis, 2026)
Background:Soft-tissue reconstruction of middle- and distal-third medial leg defects remains challenging, especially in centers without plastic surgery support. The distally based medial adipofascial flap—although not widely popular or commonly used in routine practice—is a reliable and reproducible option that can be performed by orthopedic surgeons with dedicated orthoplastic training. Methods:A retrospective observational study was conducted on 11 patients treated between May 2019 and October 2024 at a tertiary trauma center. All patients presented with soft-tissue defects of the middle or distal medial third of the leg due to fracture-related infection (FRI) or open fractures requiring orthoplastic management. All procedures were performed by trained orthopedic surgeons using a distally based medial adipofascial flap, followed by skin grafting when required. Primary outcomes included flap survival, early postoperative complications, late complications, and mid-term functional results. Minimum follow-up was 12 months. Results:Soft-tissue coverage was performed for FRI in six patients and for open fractures in five. All flaps survived and achieved definitive wound healing. Early complications occurred in seven cases, including venous congestion, partial distal necrosis, or limited graft loss; all were managed conservatively without compromising final coverage. No late flap-related complications were observed. One patient underwent below-knee amputation due to progression of pre-existing peripheral vascular disease, unrelated to flap viability. Conclusion:The distally based medial adipofascial flap is a reliable, safe, and technically straightforward solution for the reconstruction of medial leg defects. When performed by orthopedic surgeons, it enables integrated skeletal and soft-tissue management even in the absence of microsurgical services, expanding reconstructive opportunities within an orthoplastic framework.